Caracterização dos pesquisadores em tratamento temático da informação: um estudo da produção científica por meio da análise de domínio - Santarem, Luciana Garcia da Silva [UNESP] (2010)
This study aimed to characterize the brazilian scientific community on Subject Treatment of Information analyzing its production through the publication of books, book chapters, journal articles, based on bibliometric indicators. There is a worldwide trend in all areas of knowledge in evaluating the scientific production, in order to diagnose the progress in the area and followed the directions and the most productive researchers aware of the research front. In Brazil, recent studies show that different professionals are concerned not only to study its main subject, assess the information that circulates in their midst and in your area. This evaluation can be performed from bibliometric studies, relying on recent issues of domain analysis. There are some approaches, such as production of guides to literature, to epistemological studies artificial intelligence, including among them, the bibliometric studies, an approach that will be used in this study. Proceeded as follows: a survey of researchers of post-graduate in Information Science in the theme song Subject Treatment of Information; selection of scientific production from the keywords, using as instrument the researcher's own curriculum registered Database Platform; analyzed the most frequent theme addressed in the publications of books and book chapters and categorized in the keywords related to the articles by identifying themes and approaches more frequent in subjects Subject Treatment of Information, as well as consultation for the classification of WebQualis journals where researchers publish; analysis was performed of co-authorship among researchers is that the scientific community to study and rose out other partnerships. We identified the publication with colleagues from other institutions or even the institution itself; analysis was performed... (Complete abstract click electronic access below)